Molecular Phylogenetic Analysis of the Orthoptera (Arthropoda, Insecta) based on Hexamerin Sequences - Zhang, Xiaohong; Hao, Jinfeng; Xia, Yu; Chang, Yage; Zhang, Daochuan; Yin, Hong (Zootaxa, 2017)
The higher taxa classification and phylogeny of the insect order Orthoptera have long been controversial. Hexamerin, as a member of the highly conserved arthropod hemocyanin superfamily, has been shown to be a good marker for the phylogenetic study of insects. However, few studies have used hexamerins on the phylogeny of Orthoptera. In this study, we determined twenty-seven different hexamerin subunit type sequences in seventeen speices of Orthoptera. In order to infer the phylogenetic relationships among the superfamilies within Orthoptera and test the monophyly of Orthoptera, phylogenic trees were reconstructed using Neighbor-Joining (NJ) and Bayesian inference (BI) methods with two dipluran and three hymenopteran hexamerin sequences as outgroups. The result supported the monophyly of Orthoptera, which includes two monophyletic suborders Caelifera and Ensifera. The Caelifera includes Acridoidea, Eumastacoidea, Tetrigoidea and Tridactyloidea, and the Ensifera includes Tettigonioidea, Grylloidea and Gryllotalpoidea. Our study is basically consistent with the study of morphological classification. In addition, our study indicates that a relatively comprehensive taxa sampling is essential to solve some problems in phylogenetic reconstruction.